2021
DOI: 10.4103/jfmpc.jfmpc_1007_21
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and utilization of urgent care services among patients attending Al-Wazarat PHCC in Riyadh, Saudi Arabia 2020

Abstract: Background: Urgent Care Clinics (UCCs) offer unscheduled appointments with a “treat and release” length of visits not exceeding 60 min. The growth of clinics is dictated by patients’ demand for quality care that is unscheduled, expedited, and ubiquitous, making them accessible and available. Objectives: This study aimed to assess the patient's level of awareness and utilization pattern of UCCs in Wazarat Health Care Center (WHCC) and assess factors associated with them.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Most participants in this study (69.2%) reported overcrowding in PHCCs, and nearly half of them (50.3%) reported visiting PHCCs without an appointment. Albalahi et al reported similar results: about 45% of patients in their survey said they visited the UCC in Riyadh, Saudi Arabia, without making an appointment [5]. Patients were drawn to the scheduling flexibility, indicating that comparable scheduling in traditional primary care systems would also be effective in attracting patients.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Most participants in this study (69.2%) reported overcrowding in PHCCs, and nearly half of them (50.3%) reported visiting PHCCs without an appointment. Albalahi et al reported similar results: about 45% of patients in their survey said they visited the UCC in Riyadh, Saudi Arabia, without making an appointment [5]. Patients were drawn to the scheduling flexibility, indicating that comparable scheduling in traditional primary care systems would also be effective in attracting patients.…”
Section: Discussionmentioning
confidence: 72%
“…To lessen the burden on emergency rooms and shorten their long waiting times, it is advised that any non-life-threatening medical problem requiring immediate attention be taken to a UCC rather than an ED. However, given their longer office hours during the week and on weekends, which the majority of primary care physicians do not offer, it is advised to visit a UCC in addition to primary care services, rather than using a UCC as a substitute for a primary care physician [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants with lower educational attainment reported a substantially higher percentage (51.33%) of visiting primary clinics without a prior appointment than those with university and higher education backgrounds (37.68%). In terms of income, a noteworthy disparity in awareness levels was observed, with the highest awareness (32.86%) noted among participants with an income range of 6000-12000 SAR (P = 0.023) [ 24 ]. Furthermore, in another study, a comprehensive total of 1303 questionnaires were filled out, with 601 respondents indicating awareness of alternative services.…”
Section: Discussionmentioning
confidence: 99%